Molecular characterization of the UDP-glucose 4-epimerase (BrUGE) gene family in response to biotic and abiotic stress in Chinese cabbage (Brassica rapa) - Jung, Yu Jin; Kyoung, Jung Ho; Nou, Ill Sup; Cho, Yong Gu; Kang, Kwon Kyoo (Plant biotechnology reports, 2015)
UDP-glucose 4-epimerase (UGE; EC 5.1.3.2) is an enzyme that plays an essential role in the interconverts UDP-D-glucose (UDP-Glc) and UDP-Dgalactose (UDP-Gal). Five members of the Chinese cabbage (Brassica rapa) UGE gene family, designated BrUGE1 to BrUGE5, have been cloned and characterized. Quantitative PCR shows that the BrUGE1and BrUGE4 mRNA are most abundant among other BrUGE genes, accounting for more than 55 % of total BrUGE transcripts in most of the tissues examined. All genes showed organ-specific expression pattern, two of which (BrUGE1 and 4) actively responded after Pectobacterium carotovorum subsp. carotovorum infection, while four genes (BrUGE-1, -3, -4, and -5)were shown to respond considerably against salt, drought and abscisic acid treatments. To better understand the function of the UGE gene, we constructed a recombinant pART vector carrying the BrUGE1 gene under the control of the CaMV 35S promoter and nos terminator and transformed using Agrobacterium tumefaciens. We then investigated BrUGE1 overexpressing rice lines at the physiological and molecular levels under biotic and abiotic stress conditions. Bioassay of T₃ progeny lines of the transgenic plants in Yoshida solution containing 120 mM NaCl for 2 weeks, confirmed that the BrUGE1 enhances salt tolerance to transgenic rice plants. Also T₃ progeny lines of the transgenic plants, when exposed to infection caused by Xanthomonas oryzae pv. oryzae, showed tolerance to bacterial blight. These results showed that BrUGE1 can be used as potential genetic resource for engineering Brassica with multiple stress resistance.